The role of aminogenic glucagon secretion in blood glucose homeostasis - Unger, Roger H. (1969)
Hyperaminoacidemia is a powerful stimulus of pancreatic glucagon secretion. These studies were designed to elucidate the role of aminogenic hyperglucagonemia in glucoregulation. Conscious dogs with previously implanted indwelling venous catheters were employed. The results support the view that a role of glucagon is to limit blood glucose decline during hyperaminoacidemia. First, a significant negative correlation between the area of glucagon increment during the 1st 20 min of a 10 amino acid infusion and the maximum fall in glucose concentration was observed. Second, when endogenous glucagon secretion was suppressed by means of a continuous glucose infusion, hyperaminoacidemia induced a maximal glucose decline which averaged 35 mg/100 ml, differing significantly from mean maximal fall of 3 mg/100 ml, which normally occurs in the presence of endogenous hyperglucagonemia. Third, when, during hyperglycemic suppression of endogenous glucagon secretion, 50 mμg of exogenous glucagon/min was infused via the mesenteric vein with the amino acids, the fall in glucose was reduced to an average of 5 mg/100 ml. Similarly when pancreozymin, administered during the combined infusion of glucose and amino acids, overcame glucose suppression of endogenous glucagon secretion, plasma glucose did not fall. Similar results were obtained when aminogenic hyperglucagonemia was prevented by other means. Hyperlipacidemia, induced by infusing a triglyceride emulsion and giving heparin injections, also suppressed aminogenic hyperglucagonemia in two of four experiments; in these two dogs glucose fell 15 and 11 mg/100 ml. In a final group of experiments, the canine pancreas was resected except for the uncinate process, which is virtually devoid of α-cells. In two dogs, in which this procedure resulted in zero portal venous glucagon levels, the administration of amino acids and/or pancreozymin resulted in a glucose decline of 14 and 16 mg/100 ml, despite the reduced β-cell population resulting from the subtotal pancreotectomy. It thus appears that the secretion of pancreatic glucagon during hyperaminoacidemia in association with insulin secretion, serves to limit the decline of glucose concentration.